Kami sa lahat ng mataba - Eliserio, U Z. (Philippine humanities review = Rebyu ng Arte at Literatura ng Pilipinas.)
"[Eliserio] injects humor in a personal essay that dwells on rather embarrassing subject matters -- physical appearance and personal disposition. His is a funny and self-deprecating look at his body and temperament, which at the same time, questions the reader's long-held assumptions and views on weight, obscenity, and frailty." -- Introduction